2021
DOI: 10.3390/ijms22137218
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the Limits of Medical Management in HCM: A Review of Current Pharmacological Therapy Options

Abstract: Hypertrophic cardiomyopathy (HCM) is the most common monogenic cardiac disease with a highly variable phenotypic expression, ranging from asymptomatic to drug refractory heart failure (HF) presentation. Pharmacological therapy is the first line of treatment, but options are currently limited to nonspecific medication like betablockers or calcium channel inhibitors, with frequent suboptimal results. While being the gold standard practice for the management of drug refractory HCM patients, septal reduction thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Figure 2 adapts the American Heart Association/American College of Cardiology treatment recommendations for patients with symptomatic HCM and outflow obstruction to include the potential role of mavacamten. 1,[3][4][5][6][7][8][9][10][11]26 βblockers and non-dihydropyridine calcium channel blockers are relatively safe and well-tolerated therapies and were employed in most patients before they were started on additional disopyramide or septal reduction therapies. 1,[4][5][6]9 Similarly, mavacamten was mostly studied in patients who were on baseline therapy or were intolerant to β-blockers or non-dihydropyridine calcium channel blockers.…”
Section: Relevance To Patient Care and Clinical Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 adapts the American Heart Association/American College of Cardiology treatment recommendations for patients with symptomatic HCM and outflow obstruction to include the potential role of mavacamten. 1,[3][4][5][6][7][8][9][10][11]26 βblockers and non-dihydropyridine calcium channel blockers are relatively safe and well-tolerated therapies and were employed in most patients before they were started on additional disopyramide or septal reduction therapies. 1,[4][5][6]9 Similarly, mavacamten was mostly studied in patients who were on baseline therapy or were intolerant to β-blockers or non-dihydropyridine calcium channel blockers.…”
Section: Relevance To Patient Care and Clinical Practicementioning
confidence: 99%
“…In a study of 503 patients undergoing myomectomy for drug refractory HCM, extensive hypertrophy (≥30 mm, P < 0.01) and younger age (40 vs 53 years, P < 0.001) were the most significant predictors of nonresponsiveness and may portend the need for subsequent medical intervention with mavacamten or disopyramide. 26…”
Section: Relevance To Patient Care and Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Trimetazidine prevents the accumulation of protons, sodium, and calcium in muscle cells by reducing the production of free radicals. Spironolactone and N-acetylcysteine [7] also improved myocardial brosis. Mavacamten is the rst drug speci cally developed for HCM [8] .…”
Section: Introductionmentioning
confidence: 89%
“…( 12 ) Pharmacological therapies remain the first line of therapy although the options are still limited to nonspecific medications, frequently offering suboptimal results. ( 13 ) Myosin modulation with Macavamtem (Bristol Myers Squibb, New York, USA) is currently being investigated by the community, although the only Phase III trial only compared the investigational drug with placebo. ( 14 ) This, at the moment, raises important doubts and questions as this trial has only confirmed that with Mavacamten, the persistence of obstruction was high in a less symptomatic population, improvement in pVO 2 was suboptimal in a young study cohort (mean age 58 years), and the lifetime tolerance remains unassessed.…”
mentioning
confidence: 99%